NILAI-NILAI KESETARAAN GENDER DALAM PENGELOLAAN PEMBELAJARAN PAI DI SD NEGERI 200223 PADANGSIDIMPUAN - RHAMA LENASARI (Journal Education Innovation (JEI), 2025)
This study aims to examine and analyze the implementation of gender equality values in the management of Islamic Religious Education (PAI) learning at SD Negeri 200223 Padangsidimpuan. The main issues investigated are how gender equality values are applied in PAI learning, whether there is any gender bias, and how teachers make efforts to create an equitable learning environment for both male and female students. The findings show that, although there are no formal policies regarding gender equality in PAI learning at SD Negeri 200223 Padangsidimpuan, teachers have made efforts to create a classroom free from gender discrimination. Some of the steps implemented include balanced time distribution, providing equal opportunities for all students to speak and ask questions, and teaching the importance of mutual respect regardless of gender. However, several challenges, such as the persistence of gender stereotypes in society and the limited availability of educational resources that support gender equality, affect the effectiveness of these efforts. In conclusion, while teachers have tried to integrate gender equality values into PAI learning, there is a need for improved teacher training and curriculum enhancement that is more responsive to gender issues in order to achieve a more inclusive learning environment at SD Negeri 200223 Padangsidimpuan.